2019
DOI: 10.3390/molecules24122231
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential and Biological Applications of Cordycepin and Metabolic Mechanisms in Cordycepin-Producing Fungi

Abstract: Cordycepin (3′-deoxyadenosine), a cytotoxic nucleoside analogue found in Cordyceps militaris, has attracted much attention due to its therapeutic potential and biological value. Cordycepin interacts with multiple medicinal targets associated with cancer, tumor, inflammation, oxidant, polyadenylation of mRNA, etc. The investigation of the medicinal drug actions supports the discovery of novel targets and the development of new drugs to enhance the therapeutic potency and reduce toxicity. Cordycepin may be of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 194 publications
(245 reference statements)
0
53
0
Order By: Relevance
“…Both HEA and cordycepin (3ʹ-deoxyadenosine) are main components of Cordyceps species and are also analogues of adenosine. The antitumor effect of cordycepin has been widely reported, but studies on HEA antineoplastic activity are relatively few [ 6 , 23 , 24 ]. Previous studies have shown that EEC has an antitumor effect, and HEA is one of the main components of EEC, but no in-depth study has been conducted [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both HEA and cordycepin (3ʹ-deoxyadenosine) are main components of Cordyceps species and are also analogues of adenosine. The antitumor effect of cordycepin has been widely reported, but studies on HEA antineoplastic activity are relatively few [ 6 , 23 , 24 ]. Previous studies have shown that EEC has an antitumor effect, and HEA is one of the main components of EEC, but no in-depth study has been conducted [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are a few reports indicating that Cordyceps intake can cause lead poisoning in some cases. Considering the potential for toxicity, resistance and its efficiency, potential drug derivatives designed from the natural products for the adenosine deaminase-resistant properties and low-toxicity causing effects of cordycepin, as well as organ-targeted nanoparticles for cordycepin delivery for in vivo therapy, are also needed [146].…”
Section: Safety and Efficacymentioning
confidence: 99%
“…Moreover, there are a few reports indicating that Cordyceps intake can cause lead poisoning in some cases. Considering the potential for toxicity, resistance and its efficiency, potential drug derivatives designed from the natural products for the adenosine deaminase-resistant properties and low-toxicity causing effects of cordycepin, as well as organ-targeted nanoparticles for cordycepin delivery for in vivo therapy, are also needed [ 146 ]. Further clinical, experimental as well as epidemiological data are required for identification of other molecular targets to see the correlation between Cordyceps and other diseases like cancers and to estimate the validation of optimum dosing for its safety and efficacy [ 28 ].…”
Section: Safety and Efficacymentioning
confidence: 99%
“…Cordycepin can inhibit RNA synthesis and has demonstrated immense medicinal potential ( Table 1 ), including anti-cancer, anti-inflammatory, antibiotic, anti-virus, and antioxidant activities [ 31 ]. However, in addition to its dosage-dependent toxicity to different cells, cordycepin has shown an effect in stimulating testosterone production in the models of both mouse Ledydig cells and mice, which may alter male fertility [ 32 ]. Recently, it has been shown that the anti-leukemia drug pentostatin ( Figure 2 ), i.e., the 2’-deoxycoformycin originally isolated from Streptomyces antibioticus being an irreversible inhibitor of adenosine deaminase, can also be produced by C. militaris through the same BGC for cordycepin production via a protector–protégé strategy [ 19 ].…”
Section: Known Metabolites Produced By Cordyceps mentioning
confidence: 99%